High Sensitivity 0.5 to 19.5 GHz Receiver with 1.1-GHz Instantaneous Bandwidth - Volkov, V.V.; Vavriv, D.M.; Bulakh, E.V.; Kravtsov, A.A. (Радиофизика и радиоастрономия, 2014)
A wideband high sensitivity microwave receiver operating within 0.5 to 19.5 GHz and providing a 1.1-GHz instantaneous bandwidth is described. The receiver shows a noise figure as low as 10 dB and the input third-order intercept point up to 10 dBm as well. Also, the receiver is characterized by a low spurious response and extremely low residual phase noise, too. Essential design principles of the receiver are given and discussed. Описывается широкополосный высокочувствительный свервысокочастотный приемник, способный принимать сигналы в диапазоне 0.5÷19 ГГц с мгновенной полосой 1.1 ГГц. Приемник имеет коэффициент шума не превышающий 10 дБ и точку интермодуляции 3-го порядка по входу, достигающую +10 дБм. Приемник отличается также малым уровнем внутренних паразитных сигналов и крайне низкими значениями внутренних фазовых шумов. Приведены и обсуждаются основные принципы построения приемника. Описується широкосмуговий високочутливий надвисокочастотний приймач сигналів у діапазоні 0.5 ÷19 ГГц з миттєвою смугою 1.1 ГГц. Приймач має коефіцієнт шуму не вище 10 дБ та точку інтермодуляції 3-го порядку на вході, що досягає +10 дБм. Приймач характеризується також малим рівнем внутрішніх паразитних сигналів та вкрай низькими фазовими шумами. Наводяться та дискутуються основні принципи побудови приймача.